RADT-41. IATROGENIC INFLUENCE ON PROGNOSIS OF RADIATION-INDUCED CONTRAST ENHANCEMENTS IN PATIENTS WITH GLIOMA WHO 1-3 FOLLOWING PHOTON AND PROTON RADIOTHERAPY. (14th November 2022) - Eichkorn, Tanja; Lischalk, Jonathan; Deng, Maximilian; Elisabetta, Sandrini; Eva, Meixner; Regnery, Sebastian; Held, Thomas; Bauer, Julia; Bahn, Emanuel; Semi, Harrabi; Juliane, Hoerner-Rieber; Klaus, Herfarth; et al.
Abstract: Radiation-induced contrast enhancement (RICE) is a common side effect following radiotherapy for glioma, but both diagnosis and handling are challenging. Due to the potential risks associated with RICE and its challenges in differentiating RICE from tumor progression, it is critical to better understand how RICE prognosis depends on iatrogenic influence. We identified 99 patients diagnosed with RICE who were previously treated with either photon or proton therapy for World Health Organization (WHO) grade 1-3 primary gliomas. Post-treatment brain MRI-based volumetric analysis and clinical data collection was performed at multiple time points. The most common histologic subtypes were astrocytoma (50%) and oligodendroglioma (46%). In 67%, it was graded WHO grade 2 and in 86% an IDH mutation was present. RICE first occurred after 16 months (range: 1 - 160) in median. At initial RICE occurrence, 39% were misinterpreted as tumor progression. A tumor-specific therapy including chemotherapy or re-irradiation led to a RICE size progression in 86% and 92% of cases, respectively and RICE symptom progression in 57% and 65% of cases, respectively. A RICE-specific therapy such as corticosteroids or Bevacizumab for larger or symptomatic RICE led to a RICE size regression in 81% of cases with symptom stability or regression in 62% of cases. RICE progression went along with a worsening in progression-free survival (p = 0.04). While with chemotherapy and re-irradiation a RICE progression was frequently observed, anti-edematous or anti-VEGF treatment frequently went along with a RICE regression. For RICE, correct diagnosis and treatment decisions are challenging and critical and should be made interdisciplinarily.